A Devaney Chaotic System Which Is Neither Distributively nor Topologically Chaotic (Communications in Mathematical Research, 2021)
Weiss proved that Devaney chaos does not imply topological chaos andOprocha pointed out that Devaney chaos does not imply distributional chaos. Inthis paper, by constructing a simple example which is Devaney chaotic but neitherdistributively nor topologically chaotic, we give a unified proof for the results of Weissand Oprocha.